2016
DOI: 10.1182/blood-2016-03-603365
|View full text |Cite
|
Sign up to set email alerts
|

How I treat refractory immune thrombocytopenia

Abstract: This article summarizes our approach to the management of children and adults with primary immune thrombocytopenia (ITP) who do not respond to, cannot tolerate, or are unwilling to undergo splenectomy. We begin with a critical reassessment of the diagnosis and a deliberate attempt to exclude nonautoimmune causes of thrombocytopenia and secondary ITP. For patients in whom the diagnosis is affirmed, we consider observation without treatment.Observation is appropriate for most asymptomatic patients with a platele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
129
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(138 citation statements)
references
References 99 publications
0
129
0
1
Order By: Relevance
“…11,31 The present study was designed to assess the ability of the PEA to selectively identify patients considered to be HIT positive on the basis of both clinical presentation (intermediate to high 4Ts score of 4-8) and PF4 ELISA results (OD $ 2.0 or $ 1.0, depending on the 4Ts score) as recommended. 19,20,29 Using this classification, the diagnostic accuracy of the PEA was found to be significantly better than that of the SRA (AUC, 0.92 vs 0.82; P < .05) and the P-selectin expression level of 24% was found to be optimal as a threshold for defining a positive test result. A significant difference in accuracy between the PEA and SRA was maintained The greater sensitivity of the PEA for detection of platelet-activating antibodies in patients receiving heparin treatment appears to be the result of PF4-dependent priming of test platelets by a mechanism not yet fully defined, leading to enhanced antibody binding and activation via the platelet Fc receptor CD32.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,31 The present study was designed to assess the ability of the PEA to selectively identify patients considered to be HIT positive on the basis of both clinical presentation (intermediate to high 4Ts score of 4-8) and PF4 ELISA results (OD $ 2.0 or $ 1.0, depending on the 4Ts score) as recommended. 19,20,29 Using this classification, the diagnostic accuracy of the PEA was found to be significantly better than that of the SRA (AUC, 0.92 vs 0.82; P < .05) and the P-selectin expression level of 24% was found to be optimal as a threshold for defining a positive test result. A significant difference in accuracy between the PEA and SRA was maintained The greater sensitivity of the PEA for detection of platelet-activating antibodies in patients receiving heparin treatment appears to be the result of PF4-dependent priming of test platelets by a mechanism not yet fully defined, leading to enhanced antibody binding and activation via the platelet Fc receptor CD32.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Accordingly, experts in the field recommend use of PF4 ELISA OD $ 2.0 or $ 1.0 together with an intermediate or high 4Ts score (4-5 or 6-8, respectively) to optimize diagnosis. 19,20 However, a low 4Ts score, in itself, has a high negative predictive value for HIT.…”
Section: Pea Has High Diagnostic Accuracymentioning
confidence: 99%
“…ITP with recurrent clinically relevant bleedings that does not respond to multiple therapies is a serious disease with high morbidity and mortality [125,126]. In this situation, patients are usually offered a combination of ITP agents, e.g., rituximab plus steroids plus TRAs.…”
Section: Combination Therapies For Multi-refractory Itpmentioning
confidence: 99%
“…The goals of ITP treatment are to maintain the platelet count to avoid the risk of serious bleeding and to limit drug toxicity [17]. Several retrospective studies demonstrated that dapsone provides an effective, inexpensive, and well-tolerated alternative for patients with refractory ITP (Table 2) [12131415181920].…”
Section: Discussionmentioning
confidence: 99%